Words and worlds : world languages review - Marti, F. (Felix) (Bilingual education and bilingualism, 2005)
World Languages Review' examines the socio-linguistic situation of the world: to describe the linguistic diversity that currently characterizes humanity, to evaluate trends towards linguistic uniformity, and to establish a set of guidelines or language planning measures that favour the weaker or more endangered linguistic communities.